Expanding the Phenotype of Molybdenum Cofactor Deficiency in Neonates: Report of Two Cases - Chandran, Shanu; Muthanandam, Dhayaguruvasan; Ponmudi, Nithya; Kumar, Manish (Journal of Pediatric Neurology, 2021)
Molybdenum cofactor deficiency (MoCD) is a rare neurometabolic disorder characterized by intractable seizures, progressive microcephaly, tone abnormalities, facial dysmorphism, and feeding difficulties in the neonatal period. We present two different neonatal cases of MoCD with atypical presentations which could have been easily missed. One is a preterm baby admitted with features of sepsis, poor perfusion, and seizures who later developed tone abnormalities and feeding difficulty. The second is a term baby who presented with stridor, respiratory distress, and metabolic acidosis followed by intractable seizures and encephalopathy. Both babies had characteristic radiological and biochemical findings, and genome sequencing identified mutations in MOCS2 and MOCS1 genes, respectively. MoCD presenting as hypoxic-ischemic encephalopathy and cerebral palsy are well described, but its presentation in preterm with “sepsis-like features with drug-responsive seizures” in the early newborn period is not described, and can also cause unnecessary delay in the diagnosis. Its clinical presentation with “stridor, respiratory distress, and metabolic acidosis” is also described for the first time in literature.
Keywords: neonate; seizure; molybdenum cofactor deficiency; neurometabolic disorder